Sexual abuse, psychological symptoms and hopelessness among runaway female adolescents in Turkey - Koçtürk, Nilüfer (The journal of forensic psychiatry & psychology, 2022)
This seminal study from Turkey investigates sexual abuse (SA) victimization, psychological symptoms, and hopelessness in female adolescents with runaway behavior. A total of 76 female adolescent participants aged 15–18 completed the Brief Symptom Inventory (BSI) and Beck Hopelessness Scale (BHS). Among these adolescents, 63.1% (n = 48) were victims of SA, 61.8% (n = 47) had a Global Severity Index (GSI) T-score of 63 or above, and 68.4% (n = 52) had moderate–severe hopelessness. Although there was no significant difference, the SA rate was higher in those who had experienced SA before running away. ‘Intrafamilial relationship problems’ and ‘SA-related factors’ were the most frequently reported reasons for runaway behavior. Victims of SA had significantly higher scores in all BSI subdimensions and global symptom severity than those previously not SA victims. The results suggest that high levels of psychological symptoms, hopelessness, history of SA, and poor parent–child relationships are possible factors that can describe female adolescents who have run away from home. Psychosocial prevention programs involving adolescents and parents are needed to prevent at-risk female adolescents from running away from home.